Peran Tarekat Sammaniyah Dalam Perang Menteng Melawan Kolonial Belanda Di Palembang - Raudatun Jannah (Medina-te : Jurnal Studi Islam, 2017)
The background was the involvement of the Sammaniyah order in the Menteng war in 1816, indicating the political role played by the Sammaniyah order. Theologically the tarekat is a group that tries to distance itself from world affairs, while the Sammaniyah order participates in the political arena of the Palembang Sultanate. In writing this study using the method of historical research with the stages. This study is a library research (library research) using descriptive analysis. From the results of the analysis it is known that the Sammaniyah congregation at the level of society in the Sultanate of Palembang is a group of religious elites, who are capable of fostering, guiding their followers towards the path of Allah. . The Sammaniyah Order brought by Shaykh Abdul Shamad al-Palembani had a major influence and an important role in the efforts of politics against the Dutch colonialism with the teachings of jihad fi sabilillah. The role of a central figure in this case is Haji Zain who has charisma so easily invites his followers to fight colonialism. Not only as a religious leader in the Sammaniyah order, Haji Zain in the Menteng war had a role as warlord.